Characterization of essential oil recovered from fennel horticultural wastes. Issue 13 (3rd July 2019) - Cautela, Domenico; Vella, Filomena Monica; Castaldo, Domenico; Laratta, Bruna
Abstract: Fennel crop has been traditionally used as spice in cooking and fragrances, and in folk medicine for its spectrum of useful properties. Mediterranean is the elective natural cultivation area for this plant with Italy being a leader producer. A limit of this production is due to the high amount of wastes derived still rich of phytochemicals, which are usually underused. Hence, the extraction and characterization of essential oil from residues of fennel horticultural market was investigated to understand the potential profit of their recycling. Forty-eight compounds resulted for fennel oil waste, analysed by GC-FID-MS, with the most abundant among components was anethole. Other constituents contributing to fennel flavour were the monoterpenes limonene and nerol. The exploitation of this oil as a good source of bioactive compounds was assessed by means of its antioxidant power measured with DPPH test. Abstract :